Insomnia in primary care settings: Still overlooked and undertreated? - Aljohara S Almeneessier (Journal of Nature and Science of Medicine, 2018)
Background: Insomnia is a major medical problem that is often associated with low health status and increased health-care utilization. Therefore, we conducted this study to determine the frequency of insomnia in a population presenting to the primary healthcare (PHC) clinics for health problems other than sleep disorders. Methods: We interviewed 336 consecutive patients attending PHC face-to-face by trained medical students. Validated questionnaires were used to evaluate insomnia, sleep quality, and daytime sleepiness. The insomnia questionnaire classifies patients into three categories: (1) no insomnia, (2) Level I insomnia with the absence of daytime dysfunction, and (3) Level II insomnia with the presence of daytime dysfunction. Results: Level I insomnia was reported by 19.3% and Level II by 57.1%. Patients with insomnia were older and had worse sleep quality. Apart from a higher prevalence of hypertension among patients with insomnia, there was no difference in other comorbidities between those with insomnia and no insomnia. None of the included patients has reported his/her complaint of insomnia to the treating general practitioner (GP), and none of them was diagnosed with insomnia by the GP. Conclusion: Insomnia and daytime dysfunction are very common in primary care population. Despite the frequent visits of these patients to PHC, none of them has reported that he/she complains to his/her GP, and therefore, did not receive any treatment for insomnia. Education of GPs is necessary to improve recognition, diagnosis, and treatment of insomnia.